2017
DOI: 10.1039/c7gc00833c
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and recommendations for environmental sustainability assessments of pharmaceutical products in the healthcare sector

Abstract: With healthcare representing a significant portion of the global economy, it is important to be able to understand the environmental impacts of this industry due to its size and nature of its operations. Interviews with people who have intimate knowledge of the healthcare industry indicate that significant efforts and advances have been made over the past ten to fifteen years in developing environmental impact assessment methods and tools tailored for the sector. These methods and tools have been important in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 106 publications
0
36
0
1
Order By: Relevance
“…Previous limited reviews have been conducted in this space—for example, a review of recycling and waste management practices by Kwakye et al. (), a review of environmental sustainability in hospitals (mostly focused on what are considered “foreground” activities in our framework) by McGain and Naylor (), a review of pharmaceutical sustainability by De Soete, Jiménez‐González, Dahlin, & Dewulf (), and a review of environmental considerations in health technology assessment by Polisena, De Angelis, Kaunelis, & Gutierrez‐Ibarluzea (). Nonetheless, to the best of our knowledge, our review is the broadest survey to date—using a wide range of keyword searches—of this fragmented literature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous limited reviews have been conducted in this space—for example, a review of recycling and waste management practices by Kwakye et al. (), a review of environmental sustainability in hospitals (mostly focused on what are considered “foreground” activities in our framework) by McGain and Naylor (), a review of pharmaceutical sustainability by De Soete, Jiménez‐González, Dahlin, & Dewulf (), and a review of environmental considerations in health technology assessment by Polisena, De Angelis, Kaunelis, & Gutierrez‐Ibarluzea (). Nonetheless, to the best of our knowledge, our review is the broadest survey to date—using a wide range of keyword searches—of this fragmented literature.…”
Section: Discussionmentioning
confidence: 99%
“…The search was further limited to case studies performed over the last 20 years. This timeframe was chosen because existing reviews on the evolution of LCA‐application in the pharmaceutical industry have indicated the late 1990s to be the period in which the first pharma‐LCAs appeared (De Soete et al ).…”
Section: Methodsmentioning
confidence: 99%
“…With regard to the first gap relating to the lack of LCI data for API production in common LCI databases, pharma‐LCAs have so far used diverse tools (e.g., the FineChem tool [Wernet et al ] and fast LCA of synthetic chemistry [FLASC] [Curzons et al ]) and several approaches (e.g., building chemical trees) to estimate gate‐to‐gate inventories of chemicals (Jiménez‐González et al ; Jiménez‐González et al ; Ott et al ), which provide first solutions to compile process data and build inventories for pharma‐LCAs. As recommended by De Soete et al (), in the long‐run, however, LCI databases for pharmaceuticals and supplied resources (excipients, solvents, etc.) using black box data (i.e., aggregated data sets) will have to be established by third‐party companies or organizations such as the European Federation of Pharmaceutical Industries and Associations to manage and supply reliable LCI data for the pharmaceutical industry.…”
Section: Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations